2006
DOI: 10.1364/oe.14.008138
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic phase-dispersion optical coherence tomography measurements of scattering phantoms

Abstract: We demonstrate a novel technique to determine the size of Mie scatterers with high sensitivity. Our technique is based on spectral domain optical coherence tomography measurements of the dispersion that is induced by the scattering process. We use both Mie scattering predictions and dispersion measurements of phantoms to show that the scattering dispersion is very sensitive to small changes in the size and/or refractive index of the scatterer. We also show the light scattered from a single sphere is, in some c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The measured phase was converted to an estimated temperature increase using Eq. (10). The model parameters were adjusted to reflect the actual experimental conditions.…”
Section: Thermal Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The measured phase was converted to an estimated temperature increase using Eq. (10). The model parameters were adjusted to reflect the actual experimental conditions.…”
Section: Thermal Modelingmentioning
confidence: 99%
“…Typically referred to as Doppler OCT or optical Doppler tomography (ODT), these techniques analyze phase changes in the interference signal over brief time periods to detect vascular blood flow [2][3][4][5][6][7]. Endogenous OCT contrast can also be derived from variations in the size of scattering particles in the tissue [8][9][10] or wavelength-dependant absorption of different tissue components [11,12] using spectroscopic OCT [13][14][15]. Finally, non-centrosymmetric endogenous tissue components, such as collagen, can be detected using second harmonic OCT [16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we will demonstrate that the phase of the scattered signal appears to be much more sensitive to the spacing between nuclei than is the magnitude of that same signal. In previous work, we demonstrated that the scattering process is, in general, non-minimum phase, and therefore that the phase of the scattered light provides information that is not available if the magnitude alone is measured [10]. In this paper, we show that measuring both magnitude and phase provides a more complete assessment of the sample, and that measuring the full complex scattered field may provide an exceptionally sensitive indication of both nuclei size and spacing.…”
Section: Introductionmentioning
confidence: 60%
“…Spectroscopic OCT has been used to image tissue absorption from endogenous chromophores such as melanin [81], to analyze wavelengthdependent scattering [105][106][107][108], or to size cellular nuclei, which is of interest because nuclear enlargement in epithelial cells is associated with cancer [109]. Polarization-sensitive OCT is used to measure phase retardation in birefringent tissue which has application in retinal imaging [110], burn-depth determination [111], atherosclerosis imaging [112], muscular dystrophy [113], and detection of basal cell carcinomas [114].…”
Section: Optical Coherence Tomographymentioning
confidence: 99%